JORNALISMO A SERVIÇO DE QUEM? PRODUÇÃO EDITORIAL INFORMATIVA EM ASSESSORIAS DE IMPRENSA DE PREFEITURAS NO INTERIOR DO PARANÁ - Lara, Matheus Henrique de (2017)
This master thesis investigates news coverage made by five city halls communications department: Cascavel, Foz do Iguacu, Londrina, Maringa and Ponta Grossa. Those are the five biggest country towns of brazilian state of Parana. The goal was to identify the characteristics of journalism in those News productions in order to verify how journalism is made at theses kind os workplace. Journalism is here approached to the concept of Public Communication oriented to collective interest, in order to realize about the possibilities that this kind of communication should not be for personal promotion of the cities governors. Methodological stratiges include a review of Otto Groth’s (2011) concepts of “comprehension”, “natural look” and “intuition look”. Results points to a fragile news productions which is made with irresponsability concerning to the fact that it is appearently guided to personal and private interests, not the public ones.